Experimental

Algebra Level 4

a a and b b are two real numbers that are not equal to 6 6 such that a b 6 ( a + b ) + n = 0 ab - 6(a + b) + n = 0 and

a ( a 6 ) + n b ( b 6 ) + n = a 6 b 6 \large \dfrac{a(a - 6) + n}{b(b - 6) + n} = \dfrac{a - 6}{b - 6}

Calculate the value of n n .


This is part of the series: " It's easy, believe me! "


The answer is 18.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Sudeep Salgia
Jun 1, 2018

We have been given the equation, a ( a 6 ) + n b ( b 6 ) + n = a 6 b 6 \displaystyle \frac{a(a-6) + n}{b(b-6) + n} = \frac{a-6}{b-6} . Cross multiplying, we get ( a ( a 6 ) + n ) ( b 6 ) = ( b ( b 6 ) + n ) ( a 6 ) a ( a 6 ) ( b 6 ) + n ( b 6 ) = b ( a 6 ) ( b 6 ) + n ( a 6 ) \left(a(a-6) + n \right) (b-6) = \left(b(b-6) + n \right) (a-6) \implies a(a-6)(b-6) + n(b-6) = b(a-6)(b-6) + n(a-6) On rearranging, we have ( a b ) ( a 6 ) ( b 6 ) = n ( a b ) \displaystyle (a-b)(a-6)(b-6) = n(a-b) . Since a b a \neq b , we have, ( a 6 ) ( b 6 ) = n a b 6 ( a + b ) + 36 n = 0 (a-6)(b-6) = n \implies ab - 6(a+b) + 36 -n = 0 . But, we know that a b 6 ( a + b ) = n ab -6(a+b) = -n . Therefore, we can write, n + 36 n = 0 n = 18 - n + 36 -n = 0 \implies \boxed{n = 18} .

In this question. If we set a=b=12 and n=0. How about it? It is true. Because in question ,nothing explanation about (a equal to b) or ( a not equal to b). We just know that a and b not equal to 6

Rofiud Darojad - 2 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...